Presentación del quinto número de Comparative Cultural Studies - European and Latin American Perspectives - Padilla, Beatriz; Cuberos Gallardo, Francisco José; Rodríguez Cruz, Marta (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
–